Limitation of Public Service Special Assignment Charges Bond in the Form of a BUMN Persero (State-Owned Enterprises) - Arya Anggara (Yayasan Tranformasi Aksara Digital, 2024)
This study analyzes the limitations of charging Public Service Obligation (PSO) fees on State-Owned Enterprises (BUMN) in the form of Persero in Indonesia, which until now has not been specifically regulated in the law. PSO is only mentioned in the clause